STRATEGI POLITIK NEWCOMER DALAM KONTESTASI POLITIK STUDI KASUS : KETERPILIHAN ANGGOTA DPRD KOTA DENPASAR DARI PARTAI PSI PADA PEMILU 2019 - Putu Mahendra, Ida Bagus; Ali Azhar, Muhammad; Apriani, Kadek Dwita (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
An example of the existence of political contestation is the implementation of general elections. After conducting early observations, the authors found data that PSI or the Indonesian Solidarity Party managed to win two seats for Denpasar City Parliament in the 2019 Election and overthrew several incumbent candidates. The formulation of the problem in this study is how the strategy of newcomer candidates from PSI in winning seats in the Denpasar City Parliament in the 2019 Election. Based on the patterns built by PSI and looking at relevant previous studies, the author uses political marketing theory and also primordial sentiment theory so that it succeeded in obtaining research findings, first, the political parties have a large enough contribution to help wining the candidates. Second, the candidates rely on a door-to-door marketing approach. Third, there was a tendency to rely on ethnicity, religion, race, and inter-groups. Keywords : Newcomer, Political Marketing, Primordial, Denpasar City Parliament